2016
DOI: 10.28945/3456
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating mCommerce Growth in Nigeria through mMoney Usage: A Preliminary Analysis

Abstract: A general belief is that Mobile Money (mMoney) has the catalytic effect of spurring mCommerce growth and driving financial inclusion in developing nations like Nigeria. In Nigeria, mMoney service is certainly a new financial service innovation in the country, and as a result critical issues surrounding its early critical mass adoption, including its perceived usefulness, remain largely opaque. In this paper, our aim was to explore factors influencing perceived usefulness of mMoney by using the extended technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…"We get all kind of calls supposedly coming from providers but it turns out to be intruders who are able to generate codes, that should be coming from service providers which are a little bit suspicious if merchant information ends up with third parties" As alluded by the operations director "I think the encryptions back to back are not strong enough because fraudsters are able to wipe people's wallet without knowing the merchant code. I don't feel safe with the telecom company because they do not understand the banking rudiment; I will feel safe if these services are run by the banks" a statement by the operations Director This finding is similar to earlier findings on the relationship between risk and trust (see Pavlou 2003;Osakwe and Okeke 2016;Bhuvana and Vasantha 2017). These findings support proposition 3 in the model.…”
Section: Mobile Technology Characteristicssupporting
confidence: 85%
See 2 more Smart Citations
“…"We get all kind of calls supposedly coming from providers but it turns out to be intruders who are able to generate codes, that should be coming from service providers which are a little bit suspicious if merchant information ends up with third parties" As alluded by the operations director "I think the encryptions back to back are not strong enough because fraudsters are able to wipe people's wallet without knowing the merchant code. I don't feel safe with the telecom company because they do not understand the banking rudiment; I will feel safe if these services are run by the banks" a statement by the operations Director This finding is similar to earlier findings on the relationship between risk and trust (see Pavlou 2003;Osakwe and Okeke 2016;Bhuvana and Vasantha 2017). These findings support proposition 3 in the model.…”
Section: Mobile Technology Characteristicssupporting
confidence: 85%
“…Confidentiality and Safety concerns hamper merchant adoption of an online and wireless channel for a commercial transaction (Bhuvana and Vasantha 2017). Because of the shared domain of online information which merchants may be reluctant to adopt until they are convinced of self-assurance in the safety feature of the technology (Osakwe and Okeke 2016). In the mobile payment environment, merchants have to entrust all their account details, to MSPs and other players in the mobile payment context.…”
Section: Mobile Technology Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia, Al-Somali et al Laukkanen and Kiviniemi (2010) and Palani and Yasodha (2012) reported that awareness (information provided by banks) diminishes perceived risks and enhances positive user expectancy of m-banking. Osakwe and Okeke (2016) stated that users are more concerned with risk when using mobile devices and pointed out the need for awareness creation, taking into consideration the level of awareness of non-adopters and early adopters about the security and benefits of m-money. Therefore, this study hypothesizes the following:…”
Section: Awareness Of Servicesmentioning
confidence: 99%
“…Report from Digital-Capital (2014) reveals that Asian countries account for nearly half of the global m-commerce revenue, which stood at us$230 billion, while sales revenue from m-Commerce in developing countries is still at very low ebb. It has also been advocated that despite the tremendous benefits which users of m-Commerce can derive from its usage, the rate of adoption in a country like Nigeria is still low (Osakwe & Okeke, 2016) as m-Commerce is still at the infant stage in developing countries generally Wong & Hiew, 2005). For instance, experience has also indicated that many customers are still reluctant to accept this new technology notwithstanding that it has much potential in developing countries (United Nations, 2002).…”
Section: Introductionmentioning
confidence: 99%